PENGARUH SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH DAN DAMPAKNYA PADA PENYERAPAN TENAGA KERJA DI SETIAP KABUPATEN PROVINSI BALI TAHUN 2019 - Masayu Endang Apriyanti; Heru Subiyantoro; Pudji Astuti (JABE (Journal of Applied Business and Economic), 2023)
This research aims to analyze tourism on locally generated revenue and impact on employment. The large selection of tourist attractions does not automatically create demand, without good management skills. The tourism industry has strong competitiveness and will be persistent in the face of any challenges, of course, by setting the best strategy for achieving maximum business goals. This research method is carried out quantitatively with cross-data and using SPSS 22 to process secondary data sourced from BPS, library, and literature studies. The targeted research output is the tourism industry can increase its competitiveness to higher quality and provides a strong attraction for tourist to visit. The results prove that tourism competitiveness affects regional revenues and impacts employment, and data statistics prove that the results of variable X have sig. = 0,021 < 0,05, F = 16,672, which means every increase of 1 unit variable X will increase the variable Y. Â While the results of variable Y to variable Z show the value of Sig. = 0.146 > 0.05 and F = 2,598 although they have a fairly good double correlation, the correlation is not strong, and the occurrence of insignificant results, is caused by other factors that were not examined in this study.